Moi, Ruben, Brynhildur Boyce and Charles I. Arjmstrong (eds). The Crossings of Art in Ireland. - Ribeiro, Solange (ABEI Journal, 2015)
Moi, Ruben, Brynhildur Boyce and Charles I. Arjmstrong (eds). The Crossings of Art in Ireland. Oxford, Bern, Berlin, Bruxelles, Frankfurt am Main, New York, Wien: Peter Lang, 2014, 311 pp.